Case Report: Tracheal stenosis due to fibrotic bridges in a post-tracheostomy COVID-19 patient - Zuccatosta, Lina; Zamacona, Borja Recalde; Porcarelli, Francesco; Mei, Federico; Gonnelli, Francesca; Gasparini, Stefano; Di Marco Berardino, Alessandro (Frontiers in Medicine, 2022)
Tracheal stenosis is a common complication of prolonged endotracheal intubation or tracheostomy, that can be classified as simple (without cartilage involvement) or complex (with cartilaginous support involvement). We report a case of a post-COVID-19 tracheal stenosis with fibrotic bridges between the tracheal walls, creating a net within the lumen and causing significant respiratory distress. The absence of cartilaginous support involvement allowed a definitive bronchoscopic treatment with complete and permanent resolution of stenosis.